2013
DOI: 10.1310/hpj4810-848
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Lipid Emulsion in the Management of Amlodipine Overdose

Abstract: Objective: To report a case of amlodipine overdose successfully treated with intravenous lipid emulsion (ILE). Case Summary: A 47-year-old, 110 kg female ingested at least 350 mg of amlodipine with an unknown amount of ethanol. Initial blood pressure was 103/57 mm Hg, mean arterial pressure (MAP) 72 mm Hg, and heart rate 113 beats per minute. In the early clinical course, activated charcoal, intravenous fluid, and calcium boluses were administered. Worsening hypotension prompted a 100 mL bolus of 20% ILE. Stab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 28 publications
0
20
0
Order By: Relevance
“…In contrast, the results for treatment of calcium channel blocker toxicity have been more promising. Many case reports have asserted the usefulness of LRT for calcium channel blocker overdose, including verapamil, 90 , 93 , 144 149 diltiazem, 93 , 150 153 and amlodipine 136 , 149 , 154 ‐ 156 overdose. Furthermore, in experimental settings, ILE has benefited animals with IV verapamil toxicity 157 .…”
Section: Part Iii: Clinical Futurementioning
confidence: 99%
“…In contrast, the results for treatment of calcium channel blocker toxicity have been more promising. Many case reports have asserted the usefulness of LRT for calcium channel blocker overdose, including verapamil, 90 , 93 , 144 149 diltiazem, 93 , 150 153 and amlodipine 136 , 149 , 154 ‐ 156 overdose. Furthermore, in experimental settings, ILE has benefited animals with IV verapamil toxicity 157 .…”
Section: Part Iii: Clinical Futurementioning
confidence: 99%
“…[7][8][9] In the largest aggregation of cases, Cave et al 7 reported that intravenous lipid emulsion improved Glasgow Coma Scale ratings and increased systolic blood pressure during treatment of nonlocal anesthetic overdose in 38 patients. The average dose of lipid used in these cases was 531 mL (SD 22 mL), which is within ranges recommended by professional societies.…”
mentioning
confidence: 99%
“…Due to the lipophilic nature of amlodipine, lipid emulsion rescue therapy was administered. Though benefits of ILE in critical patients ingested amlodipine has been presented in several reports [17][18][19][20] the only noticeable effect in our patient was transient, unsustainable increase of blood pressure.…”
Section: Discussionmentioning
confidence: 50%